Upaya Kepemimpinan PT Surya Bangun Pertiwi (SBP) Dalam Mengatasi Permasalahan Tanah: Studi Kasus: Konflik Masyarakat Busung dengan PT.Surya Bangun Pertiwi (SBP) - Ajeng Aprianingsih; Aprillia Aprillia (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Company PT. Surya Bangun Pertiwi (SBP) experienced problems or conflicts with the Busung village community regarding land, namely land distribution that had not been realized, as well as allegations of fraud regarding land ownership in 2023. PT. Surya Bangun Pertiwi (SBP) made several efforts to overcome this problem, such as handing over replacement land, handing over land certificates, and handing over land location maps. Apart from that, the people of Busung village are also making efforts to improve their welfare through developing collaborative management in managing the Telaga Biru Desert. In resolving land issues with the Busung village community, PT.SBP and the Busung village community must pay attention to factors such as transparency and justice, community participation, legal certainty, cooperation and collaboration, as well as natural resource management so that the efforts made can be successful and have an impact. positive for both parties.